Ochrona wolności i praw jednostki - Węgrzyn, Justyna; Jabłoński, Mariusz (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The US Constitution is composed of a preamble, 7 articles and 27 amendments. Besides the issues related to authorities of power in the State, an essential matter for these points such as: freedoms and rights of citizens, which are included in the first 10 amendments to the Constitution. Due to the clarification of constitutional freedoms, the authors addressed to the decisions of the Supreme Court of the United States. Furthermore, in this research paper, they were presented the views on the essence of freedom and the principles of its protection. The main aim of this article, it was to characterize the constitutional range of regulation in the area of freedom and individual rights, not only in the US Constitution, but also in the Constitution of the Republic of Poland of 2nd April, 1997.
Keywords: protection of rights; jurisprudence Supreme Court; freedom; constitutional freedom